Dilation‐Responsive Microshape Programing Prevents Vascular Graft Stenosis. Issue 18 (17th March 2021) - Yi, Se Won; Shin, Young Min; Lee, Jung Bok; Park, Ju Young; Kim, Dae‐Hyun; Baek, Wooyeol; Yoon, Jeong‐Kee; Kim, Deok Gie; Shin, In Sik; Kim, Chang‐Soo; Kang, Mi‐Lan; Yang, Jae Won; et al.
Abstract: Shape memory materials have been successfully applied to minimally invasive implantation of medical devices. However, organ‐movement‐specific shape programing at a microscale level has never been demonstrated despite significant unmet needs. As vein‐to‐artery grafting induces vein dilation and stenosis, a polymeric self‐enclosable external support (SES) is designed to wrap the vascular out‐wall. Its micropores are programmed to increase sizes and interconnections upon dilation. Vessel dilation promotes venous maturation, but overdilation induces stenosis by disturbed blood flow. Therefore, the unique elastic shape‐fixity of SES provides a foundation to enable a stable microscale shape transition by maintaining the vein dilation. The shape transition of micropore architecture upon dilation induces beneficial inflammation, thereby regenerating vasa vasorum and directing smooth muscle cell migration toward adventitia with the consequent muscle reinforcement of veins. This game‐changer approach prevents the stenosis of vein‐to‐artery grafting by rescuing ischemic disorders and promoting arterial properties of veins. Abstract : The elastic self‐enclosable external wrapping support (SES) enables organ movement‐specific shape programing in a microscale, thereby preventing vascular stenosis in vein‐to‐artery grafting by approaching the out‐wall side of vessel. The dilation‐responsive shape transition of micropores in support induces beneficial inflammation, regenerating vasa vasorum and directing smooth muscle cell migration toward neoadventitia with consequent muscle reinforcement of vein.